Bee Venom Melittin Disintegrates the Respiration of Mitochondria in Healthy Cells and Lymphoblasts, and Induces the Formation of Non-Bilayer Structures in Model Inner Mitochondrial Membranes - Gasanoff, Edward; Liu, Yipeng; Li, Feng; Hanlon, Paul; Garab, Győző (International journal of molecular sciences, 2021)
In this paper, we examined the effects of melittin, a bee venom membrane-active peptide, on mitochondrial respiration and cell viability of healthy human lymphocytes (HHL) and Jurkat cells, as well as on lymphoblasts from acute human T cell leukemia. The viability of melittin-treated cells was related to changes in O2 consumption and in the respiratory control index (RCI) of mitochondria isolated from melittin-pretreated cells as well as of mitochondria first isolated from cells and then directly treated with melittin. It was shown that melittin is three times more cytotoxic to Jurkat cells than to HHL, but O2 consumption and RCI values of mitochondria from both cell types were equally affected by melittin when melittin was directly added to mitochondria. To elucidate the molecular mechanism of melittin's cytotoxicity to healthy and cancer cells, the effects of melittin on lipid-packing and on the dynamics in model plasma membranes of healthy and cancer cells, as well as of the inner mitochondrial membrane, were studied by EPR spin probes. The affinity of melittin binding to phosphatidylcholine, phosphatidylserine, phosphatidic acid and cardiolipin, and binding sites of phospholipids on the surface of melittin were studied by 31P-NMR, native PAGE and AutoDock modeling. It is suggested that the melittin-induced decline of mitochondrial bioenergetics contributes primarily to cell death; the higher cytotoxicity of melittin to cancer cells is attributed to its increased permeability through the plasma membrane.
Keywords: Mitochondria; Lipid Bilayers; EPR; inner mitochondrial membranes; Humans; Lymphocytes; lymfocyty; buněčné dýchání; permeabilita; Jurkat buňky; melittin; 31P-NMR; Permeability; Blood Cells; T cell leukemia; Models, Biological; Bee Venoms; krevní buňky; Jurkat Cells; lidé; mitochondrie; mitochondrial bioenergetics; Cells, Cultured; Melitten; Mitochondrial Membranes; lipidové dvojvrstvy; native PAGE; AutoDock modeling; respiratory control index; mitochondriální membrány; kultivované buňky; biologické modely; melitten; cytotoxicity; včelí jedy; Cell Respiration